دلالة أبنية المشتقات العاملة في سورة الكهف دراسة تطبيقية - بكوش,حسني; بن علي,عبد الله; هاشم,سعيدة (University of Eloued جامعة الوادي, 2024)
تتناول هذه الدراسة أبنية المشتقات العاملة في اللغة العربية: دلالة ومعنى من خلال تطبيقها على سورة الكهف من القرآن الكريم وحاولت أن تسلط الضوء على المشتقات في اللغة العربية، فدرست حدودها وانواعها وصيغها الوظيفية كما ركزت على إحصاء المشتقات العاملة في سورة الكهف وإبراز كيفية توليدها للمعاني والدلالات من خلال توظيفها في آيات سورة الكهف، كما أحصت بعض أقوال المفسرين وخاصة اللغويين منهم، أحصت أقوالهم في توجيه أبنية المشتقات في سورة الكهف وكيفية توليد الدلالة من خلال تتبع سياقاتها في الآيات. This study deals with the structures of derivatives operating in the Arabic language: meaning and significance through its application to Surat Al-Kahf from the Holy Quran. It tried to shed light on derivatives in the Arabic language, so it studied their limits, types and functional forms. It also focused on enumerating the derivatives operating in Surat Al-Kahf and highlighting how they generate meanings and connotations through their use in the verses of Surat Al-Kahf. It also enumerated some of the sayings of the interpreters, especially the linguists among them. It enumerated their sayings in directing the structures of derivatives in Surat Al-Kahf and how to generate meaning by following their contexts in the verses
لسانيات عامة
Keywords: أبنية المشتقات سورة الكهف توليد الدلالة; Derivative structures Surat AlKahf Generating meaning